2007
DOI: 10.1100/tsw.2007.184
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoid Receptors in the Human Vascular Wall

Abstract: The mechanisms involved in vascular homeostasis and disease are mostly dependent on the interactions between blood, vascular smooth muscle, and endothelial cells. There is an accumulation of evidence for the involvement of prostanoids, the arachidonic acid metabolites derived from the cyclooxygenase enzymatic pathway, in physiological and/or pathophysiological conditions. In humans, the prostanoids activate different receptors. The classical prostanoid receptors (DP, EP1–4, FP, IP, and TP) are localized at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 150 publications
1
93
0
1
Order By: Relevance
“…Earlier evidence suggested that PTGER4 mRNA is ubiquitously expressed in a variety of tissues and in most immune cell types [10,11]. In our study, it was shown that ChPTGER4 was ubiquitously expressed in all tested C. hongkongensis tissues including the gill, mantle, heart, adductor muscle, digestive gland, gonad and hemocytes, which is consistent with previous reports in mammals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Earlier evidence suggested that PTGER4 mRNA is ubiquitously expressed in a variety of tissues and in most immune cell types [10,11]. In our study, it was shown that ChPTGER4 was ubiquitously expressed in all tested C. hongkongensis tissues including the gill, mantle, heart, adductor muscle, digestive gland, gonad and hemocytes, which is consistent with previous reports in mammals.…”
Section: Discussionsupporting
confidence: 93%
“…The biological actions of PGE2 are mediated by four distinct prostanoid E receptors (EP), termed PTGER1-4 (also known as EP1-4), all of which have seven transmembrane-spanning domains [7,8] and are coupled to a variety of intracellular signal transduction pathways including those that induce increases in cAMP (PTGER2 and PTGER4), decreases in cAMP (PTGER3) and of Ca 2þ mobilization (PTGER1) [8,9]. Among the PTGERs, PTGER4 is the most abundantly expressed EP subtype in a variety of immune cell types, and its functional responses have been reported in B-and T-lymphocytes, eosinophils, monocytes and macrophages [10,11]. It was reported that the PTGER4 has several sites, including S103, T168, Y186, F191, L195, S285, and D311, which were identified as being essential of the interaction of PGE2 [12].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Mizuguchi, et al revealed that myoelectrical activity was suppressed by continuous infusion of ONO-DI-004 into the gastric artery. This demonstrates that EP1 signaling has a crucial role in the suppression of myoelectrical activity of gastric smooth muscles and inhibition of gastric emptying.…”
Section: Synthesized Ep Agonists I) Ep1 Agonistsmentioning
confidence: 99%
“…The EP3 receptor is coupled to the Gi protein and its activation increases the intracellular levels of Ca 21 . The EP3 receptor itself has several splice variants exhibiting some constitutive activity [16,17]. At the cellular level and in murine allergic inflammation, PGE 2 was found to inhibit eosinophil trafficking via EP2 receptor activation [18].…”
Section: Introductionmentioning
confidence: 99%